Pengaruh Prinsip Self Assessment terhadap Pemenuhan Kewajiban Zakat - Alifio, Muhammad Iqbal; Prabowo, Prayudi Setiawan (Universitas Negeri Surabaya, 2020)
The fluctuation of the level of zakat funds obtained by BAZNAS affects the zakat potential that has been determined. The National Zakat Agency (BAZNAS) revealed that the potential for zakat in Indonesia can get IDR 252 trillion per year, while the funds raised are only 1% of the potential zakat. That is, the zakat potential which is set in the year has not reached the fulfillment of zakat obligations, therefore this study aims to determine the principle of self-assessment of the fulfillment of zakat obligations partially or simultaneously. This type of research uses associative quantitative methods with the sampling technique using random sampling. The required sample is 100, the respondents are Muslim communities who have fulfilled their zakat fitrah obligations domiciled in Gresik and Surabaya. Research using multiple linear models to obtain answers to research objectives. The results obtained partially and simultaneously there is an influence from the variable of the principle of self-assessment on the fulfillment of zakat obligations. The results of the R2 test, the independent variable has an effect of 0.306 or 30.6% on the dependent variable. While there is a residual of 0.694 or 69.4%, it can be seen that other factors are outside the research.